PERSON-ORGANIZATION FIT AND JOB BURNOUT AS PREDICTORS OF QUIET QUITTING IN VOCATIONAL EDUCATION - Zhou , Jing; Soo , Hooi Sin; Aziz , Azelin Binti (Bangladesh Journal of Multidisciplinary Scientific Research, 2025)
In recent years, the phenomenon of quiet quitting, characterized by employees’ psychological disengagement while continuing to meet only the minimum job requirements, has garnered increasing attention in organizational research. Despite its growing relevance, empirical studies examining this behavior within the context of vocational education remain limited, particularly in China. This study examines the relationships between person-organization fit (P-O fit), work overload, job burnout, and quiet quitting among faculty members in Chinese vocational colleges. A cross-sectional survey design was employed, and data were collected from 588 teaching staff members using structured questionnaires. Partial least squares structural equation modeling (PLS-SEM) was applied to analyze the hypothesized relationships among the variables. The results show that P-O fit is significantly and negatively associated with quiet quitting, both directly (β = –0.274, p < 0.001) and indirectly through the reduction of job burnout (β = –0.191, p < 0.001). Although work overload does not have a significant direct effect on quiet quitting (β = 0.105, p = 0.113), it exhibits a significant indirect effect through job burnout (β = 0.202, p < 0.001), which acts as a key mediating variable. Additionally, job burnout demonstrates a strong, positive relationship with quiet quitting behavior (β = 0.462, p < 0.001). These findings suggest that alignment between individuals and organizations, along with effective management of job-related strain, is key to understanding quiet quitting among vocational lecturers. This research contributes to the limited empirical literature on quiet quitting in Chinese vocational education and provides a quantitative assessment of the underlying organizational and psychological mechanisms involved. The study contributes theoretically by extending the Conservation of Resources (COR) theory, validating burnout as a mediating mechanism between organizational stressors and withdrawal behaviors in the underexplored context of Chinese vocational education. Practically, it offers actionable insights for reducing quiet quitting through improved P-O fit, balanced workload management, and early intervention for burnout. JEL Classification Codes: M5, M540, C3, I2.